Heavy metal cation probe with signal to noise ratio measurement of fiber Bragg grating - Yang, Jingyi (2018)
An intensity-modulated Nickel ions (Ni2+) probe is experimentally demonstrated by using optical fiber Bragg grating (FBG) cascaded by a cleaved fiber end which is functionalized by multilayers of chitosan/poly acrylic acid (PAA). The multilayer film can effectively adsorbed Ni2+ that modulate signal to noise ratio (SNR) of the FBG. The proposed probe exhibits an enhanced sensitivity with detection limitation of 0.01 mM. This kind of relative measurement method contributes to eliminate power fluctuation of the optical source. Temperature can be monitored simultaneously by wavelength shift, which is benefit to minimize temperature cross effect on Ni2+ detection in the future.